Studi Redesain Tempat Penyimpanan Sementara (TPS) Limbah B3 sesuai dengan Limbah yang Dihasilkan dan Peraturan Terbaru di PT X - Miyana, Ade Wahyu Achmad; Kusuma, Maritha Nilam (Environmental Engineering Journal ITATS, 2024)
PT. X is a private company engaged in the manufacturing of machinery, equipment, and other supplies, located in one of the sub-districts in the western part of Surabaya, with a total land area of 2011,11 m². In accordance with Government Regulation Number 22 of 2021 concerning the Administration of Environmental Protection and Management, one critical activity in the management of hazardous and toxic waste is temporary storage. The purpose of designing a temporary storage facility for hazardous and toxic waste (B3) is to reduce the risk of environmental contamination and safety and health hazards for workers due to the release of B3 waste into the environment. PT. X's industry already has a permit for B3 waste storage with a capacity of 21 m³, having dimensions of 3.1 m in length, 2.7 m in width, and 2.5 m in height, and currently holds permits for only 11 types of waste. Given the existing conditions, there are several types of waste that still do not have storage permits. Since there are some types of waste that are not yet managed, PT. X is undertaking a redesign of the temporary B3 waste storage facility. PT. X manages 26 types of waste, including used lubricating oil, B3-contaminated waste (flammable solids) – seals, gaskets, hydraulic hoses, B3-contaminated waste – used resin, used B3 containers (flammable solids) – used oil containers, thinners, painting sludge, metal powder from grinding processes, used rags, production sludge including manufacturing, assembly, and maintenance, production residues including manufacturing, assembly, and maintenance, soldered PCB cuttings, solder scrap, assembly production sludge, Cathode Ray Tubes (CRT), Printed Circuit Boards (PCB), metal cable and insulation waste, B3-contaminated waste (toxic) – welding wire residue, used B3 containers (toxic) – housekeeping containers and paint containers, wastewater treatment sludge, used TL lamps, electronic waste, incandescent and LED bulbs, used cartridges, used air filters, used ink containers, used batteries, and used accumulators. Therefore, it is necessary to expand the B3 waste temporary storage area to dimensions of 4 meters in length, 5 meters in width, and 3 meters in height.